Metallurgy of the Grey Cast Iron for the Automotive Parts - Machuta, J.; Nová, I. (Металлофизика и новейшие технологии, 2017)
The melt metal is a complex solution, which may contain for the production of high-quality grey iron a number of unsuitable elements. The molten cast iron contains areas enriched with carbon, higher amount of silicon in local areas, manganese, sulphur, and phosphorus. These elements can adversely affect the properties of the produced iron for the automotive industry. The oxygen activity, hardness, tensile strength, viscosity, chemical composition, and other physical and mechanical properties of cast iron are studied. Расплавленный металл представляет собой комплексный раствор для производства высококачественного серого чугуна, который может содержать ряд нежелательных элементов. В расплавленном чугуне находятся области, обогащённые углеродом, большое количество кремния в отдельных участках, марганец, сера и фосфор. Эти элементы могут отрицательно влиять на свойства чугуна, используемого в автомобильной промышленности. Изучены активность кислорода, твёрдость, прочность на растяжение, вязкость, химический состав, а также другие физические и механические свойства чугуна. Розтоплений метал є комплексним розчином для виробництва високоякісного сірого чавуну, який може містити ряд небажаних елементів. У розтопленому чавуні є області, збагачені вуглецем, велика кількість кремнію в окремих ділянках, манган, сірка та фосфор. Ці елементи можуть мати неґативний вплив на властивості чавуну, який використовується в автомобільній промисловості. Вивчено активність кисню, твердість, міцність на розтягнення, в’язкість, хемічний склад, а також інші фізичні та механічні властивості чавуну.